Inter watershed water transfer can pave the way for doubling farmers’ income in NW Himalayas - SINGH, D. V.; PATRA, S.; SHARMA, N K; KADAM, D. M.; OJASVI, P R (Journal of Soil and Water Conservation, 2020)
Water harvesting plays a key role in the hills to meet domestic, livestock and irrigation needs. But there are inherent demerits and limitations with commonly adopted water harvesting systems. Presently in Uttarakhand, only 10-12% agricultural lands are irrigated in hill districts even when water surplus exists in many micro-watersheds of this Himalayan ecosystem. Hence, it was tried to increase water availability in deficit area by adoption of inter watershed water transfer through HDPE pipe line. Two villages (Hattal and Sainj) from Jounsar tribal region of Uttarakhand state were selected during 2013. These villages were socio-economically backward and water scarcity problem found to be the most vital issue. About 270 families were inhabited in these villages and more than half of them were engaged in traditional crop cultivation under rainfed condition. After intervention of inter watershed water transfer, a total of 670 m3 water per day was made available to the farmers which has led to 3.17 times increase in net irrigated area. Farmers had adopted the cultivation of off-season vegetables in about 35 ha area. After four years of project period, during 2017, these farmers had produced tomato, cauliflowers and other vegetables worth of Rs 411.08 lakhs. Average family income from agriculture has risen to 4.28 times during last four years. Reverse migration of 17 families has been observed in Sainj village where most of the farmers had abandoned their fields due to water scarcity before project interventions